PERAN DAN KONTRIBUSI OIF UMSU DALAM PENGENALAN ILMU FALAK DI SUMATERA UTARA - Muhammad Qorib; Zailani Zailani; Radiman Radiman; Amrizal Amrizal; Arwin Juli Rakhmadi (Universitas Muhammadiyah Prof Dr Hamka, 2019)
Astronomy is counted as a natural science that always gets the most attention of humans all the time. Lately, in Indonesia began to appear astronomical observatories that examine various things. The Falak Observatory of the University of Muhammadiyah North Sumatra (OIF UMSU) is one that has played an important role in the development of astronomy in Indonesia, especially in North Sumatra. In this observatory there are classical and modern astronomical tools. Among the role and contribution of this observatory is to provide information for students about the phenomenon and importance of astronomy, then training for students, astronomy studies, and others. The existence of this observatory is basically an appreciation of science and technology that are part of civilization.